Impact of hygienic milk production training on knowledge, attitudes and practices of women farmers in the central highlands of Ethiopia - Keba, Abdi; Tola, Alganesh; Kaylegian, Kerry E.; Kebede, Muluken; Zewdu, Ashagrie (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood safety remains a challenge in developing nations, including Ethiopia, where dairy products are known to be contaminated with foodborne pathogens. Limited food safety interventions studies for improving food safety along the food supply chain have been conducted. The objective of this intervention study was to improve the knowledge, attitudes, and practices (KAPs) of women dairy farmers in the central highlands of Ethiopia by developing and delivering training customized to their education level.MethodsA total of 120 dairy women farmers were recruited from local milk cooperatives and milk collection centers at four study sites. Training materials on clean milk production and hygienic milking practices were developed for an audience that may not be able to read or write. The 3-day curriculum was delivered using theoretical lecturing, video presentation, practical activities, and handouts, and learning was assessed with a questionnaire and checklist.ResultsThe study indicated that women dairy farmers improved their knowledge, attitude, and practices relating to quality milk production. However, milk shade assessments of individual farmers identified many important risk factors for clean milk production that were due to infrastructure issues.DiscussionThe effectiveness of the training materials and approach was supported by the increase in KAPs assessment scores from pre-training to post-training for all study sites. Comparisons of the training outcomes and evaluation results of milk shades were found counterintuitive, which revealed the complexity of food safety interventions. Customized food safety training is effective but should be combined with dairy farming infrastructure improvements to achieve the goal of clean milk production at farm level.